A refined Moving Particle Pressure Mesh (MPPM) method for solving incompressible Navier-stokes equations - Ng Y.L.; Ng K.C.; Sheu T.W.H. (Elsevier Ltd, 2023)
Data transfer; Functions; Incompressible flow; Interpolation; Mesh generation; Navier Stokes equations; Viscous flow; 'current; Eulerian grids; Incompressible (Navier )Stokes equation; Incompressible Navier Stokes equations; Moving particle pressure mesh; Moving particles; Particle pressure; Particle-based methods; Pressure solution; Radial basis function interpolation; Radial basis function networks